Managing previously unmanaged collections : a practical guide for museums - Kipp, Angela A. (Rowman & Littlefield Publishers, 2016)
Congratulations, it's your mess now! -- A first glimpse -- Back at the desk -- Getting organized -- Diving into the collection -- The power of coffee -- Getting stuff done -- Storage wants and storage needs -- We had nothing -- Failing successfully -- Success stories